2012
DOI: 10.1155/2012/161062
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Antistress and Hepatoprotective Effects of Schisandra Lignans Was Related with Its Antioxidative Actions in Liver Cells

Abstract: The present study was conducted to investigate the relationship between the anti-stress and hepato-protective effects of Schisandra Lignans Extract (SLE) on stress-induced liver damage. Seven weeks old male mice were fixed in a restraint tube for 18 h to induce liver damage. SLE was orally administered to animals for 5 days at dosages of 100 and 200 mg/kg/day before exposed to restraint stress. Oral administration of SLE significantly reduced restraint-induced liver damage in experimental animal. SLE was furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…According to the above contents, it is not difficult to find that lignans can activate the Nrf2 signaling pathway and enhance the expression of HSPs to play an antioxidant role. In addition, it was reported that lignans (100 and 200 mg/kg) isolated from SC could prevent excessive production and accumulation of free radicals in hepatocytes [185] . Schidandrin B (0.04 mmol/kg) can directly eliminate ROS and enhance the antioxidant defense system [186] .…”
Section: Othersmentioning
confidence: 99%
“…According to the above contents, it is not difficult to find that lignans can activate the Nrf2 signaling pathway and enhance the expression of HSPs to play an antioxidant role. In addition, it was reported that lignans (100 and 200 mg/kg) isolated from SC could prevent excessive production and accumulation of free radicals in hepatocytes [185] . Schidandrin B (0.04 mmol/kg) can directly eliminate ROS and enhance the antioxidant defense system [186] .…”
Section: Othersmentioning
confidence: 99%
“…In China since the XVI century this plants has belonged to the first category of drugs recommended for restoration of vitality. According to modern research, the biologically active compounds of S. chinensis have anticancer, antimicrobial action, improve the functioning of the pancreas, stimulate insulin secretion, and prevent complications in diabetic diseases (Panossian, 2008;Venkanna et al, 2014;Lv et al, 2015;Nowak et al, 2019), as well as showing hepatoprotective effects (Pu et al, 2012) and antiviral activity (Li & Peng, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Schisandra chinensis ( S. chinensis ) is a traditional Chinese herbal medicine that has been used for the treatment of viral and chemical liver injury in Asia for thousands of years [ 16 18 ]. The lignans as the main active ingredients in S. chinensis have various pharmacological effects such as antioxidative, anti-inflammatory, antitumor, and hepatoprotective activities [ 18 , 19 ]. It was reported that S. chinensis exerted its effect against chemical-induced liver injury by regulating the antioxidation function and heat shock proteins [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%